The evolution of self-injurious behaviors in people with intellectual disability and epilepsy: A follow-up study. (November 2020) - Buono, Serafino; Zagaria, Tommasa; Recupero, Marilena; Elia, Maurizio; Kerr, Mike; Di Nuovo, Santo; Ferri, Raffaele
Highlights: Self-Injurious Behaviours (SIBs) have been found to be substantially stable over time. Frequency of SIBs and level of intellectual disability show a positive correlation over time. No correlation between SIBs ( frequency and intensity ) and seizure frequency over time. Abstract: Purpose: Longitudinal studies of the evolution of Self-Injurious Behaviors (SIBs) in people with Intellectual Disability (ID) and epilepsy are not common. This study aimed to analyze the evolution (in terms of remission and persistence) and changes in the type, localization, frequency, and intensity of SIBs. Methods: SIBs were assessed in a sample of 52 people with ID and epilepsy, and re-evaluated after a seven-year interval, using the "Scale for the Assessment of Self-Injurious Behaviors". The scale was administered to caregivers (parents or health professionals) through a semi-structured interview conducted by a specifically trained psychologist. Results: The most frequent types of SIBs identified were: self-biting, self-hitting with objects, self-hitting with hand, object-finger in cavities. The main localizations of SIBs were: hands, mouth, head and cheeks. SIBs were found to be maintained after seven years, for type, localization, frequency, and intensity, in 90.4% of the sample. SIB types were stable over time, as were the affected areas. Global SIB frequency and intensity scores were found to be unchanged. Finally, a positive correlation was found between the frequency of SIBs and levels of intellectual disability. SIBs ( frequency and intensity ) and seizure frequency showed no correlation. Conclusion: Given the negative impact of SIBs on the adaptation and quality of life of people with ID and epilepsy, we believe that further studies on biological, psychological and environmental aspects are needed in order to identify any potential factors that might explain the persistence of SIBs and to find effective interventions to reduce them.